2021
DOI: 10.1039/d1nr05227f
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the structural stability of cage-like Au144 clusters

Abstract: Formation of cage-like 144-atom gold cluster is due to thermodynamic selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The size-induced evolution of electronic structure and optical properties of atomically precise gold nanoclusters constitute a central topic in nanoscience [1][2][3][4] since the breakthroughs on the structure determination of Au 102 (SR) 44 , Au 25 (SR) 18 and Au 38 (SR) 24 (where, -SR represents thiolate). [5][6][7][8] Thus far, a rich library of Au n (SR) m nanoclusters has been constructed, [9][10][11][12] which provides great opportunities for structure-property correlation and deep understanding the functionality of such materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The size-induced evolution of electronic structure and optical properties of atomically precise gold nanoclusters constitute a central topic in nanoscience [1][2][3][4] since the breakthroughs on the structure determination of Au 102 (SR) 44 , Au 25 (SR) 18 and Au 38 (SR) 24 (where, -SR represents thiolate). [5][6][7][8] Thus far, a rich library of Au n (SR) m nanoclusters has been constructed, [9][10][11][12] which provides great opportunities for structure-property correlation and deep understanding the functionality of such materials.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Thus far, a rich library of Au n (SR) m nanoclusters has been constructed, [9][10][11][12] which provides great opportunities for structure-property correlation and deep understanding the functionality of such materials. [13,14] To investigate the evolution from nonmetallic to metallic state in Au n (SR) m nanoclusters, [15][16][17][18] the determination of their HOMO-LUMO gaps (E g ) is essential, which has been accomplished by several methods, such as the optical absorption and electrochemical analysis. [19][20][21][22] But these direct measurements met difficulties in dealing with ultrasmall E g (e. g., < 0.3 eV) due to the resolution of those methods and sample heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, they found that the Au-Au distances in the Au 12 core (2.7470-2.7587 Å) are shorter than the average Au-Au distance of bulk face-centered cubic gold (2.884 Å), which also suggests that the bonding is more molecular than metallic. Deng et al 53 found that the origin of the structural stability of Au 144 (SR) 60 and Au 144 (C^CR) 60 is due to the thermodynamic stability by applying DFT energy calculation and energy decomposition analysis (EDA); in addition, they also suggested that the Au 144 NCs are unique in size because the larger (Au 279 ) and smaller (Au 130 , Au 133 ) gold NCs both prefer the center-lled gold polyhedrons. Recent work by Du et al 54 reported temperaturedependent (room temperature to 2.5 K) absorption spectra, in which they observed several new features at cryogenic temperatures, which provides strong evidence of discrete energy levels within Au 144 PET 60 (where, PET ¼ SCH 2 CH 2 Ph).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the stability of the Au 317 cluster is assessed from calculation of averaged formation energy (E ave ), which has been recently used to understand the stability difference between Au 144 and Au 145 clusters. 37 The E ave is calculated based on reaction eqn (1), where the E Aun(SR)m is the electronic energy of a cluster Au n (SR) m , and E HSR , E [SR] −, E [H] − and the E [Au (I) SR] are the electronic energies of HSR, SR − , H − and the Au-SR, respectively. Fig.…”
mentioning
confidence: 99%